Chitosan-alginate membranes accelerate wound healing - Caetano, Guilherme Ferreira; Cipriani Frade, Marco Andrey; Moretti Andrade, Thiago Antonio; Leite, Marcel Nani; Bueno, Cecilia Zorzi; Moraes, Angela Maria; Ribeiro-Paes, João Tadeu [UNESP] (Wiley-Blackwell, 2015)
The purpose of this study was to evaluate the efficacy of chitosan-alginate membrane to accelerate wound healing in experimental cutaneous wounds. Two wounds were performed in Wistar rats by punching (1.5 cm diameter), treated with membranes moistened with saline solution (CAM group) or with saline only (SL group). After 2, 7, 14, and 21 days of surgery, five rats of each group were euthanized and reepithelialization was evaluated. The wounds/scars were harvested for histological, flow cytometry, neutrophil infiltrate, and hydroxyproline analysis. CAM group presented higher inflammatory cells recruitment as compared to SL group on 2(nd) day. On the 7(th) day, CAM group showed higher CD11b(+) level and lower of neutrophils than SL group. The CAM group presented higher CD4(+) cells influx than SL group on 2(nd) day, but it decreased during the follow up and became lower on 14(th) and 21(st) days. Higher fibroplasia was noticed on days 7 and 14 as well as higher collagenesis on 21(st) in the CAM group in comparison to SL group. CAM group showed faster reepithelialization on 7(th) day than SL group, although similar in other days. In conclusion, chitosan-alginate membrane modulated the inflammatory phase, stimulated fibroplasia and collagenesis, accelerating wound healing process in rats. (c) 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 1013-1022, 2015.
Keywords: wound healing; chitosan; alginate; membrane; collagen